Take a pencil put it on the paper then make sure the ink is on the paper then write
It's B I got it right on my test
Answer: 79
Concept:
Here, we need to understand the idea of evaluation.
When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.
Solve:
<u>Given information</u>
10x² - 7x + 10
x = 3
<u>Substitute the value into the expression</u>
= 10 (3)² - 7 (3) + 10
<u>Simplify by multiplication</u>
= 10 (9) - 21 + 10
= 90 - 21 + 10
<u>Simplify by subtraction</u>
= 69 + 10
<u>Simplify by addition</u>
= 79
Hope this helps!! :)
Please let me know if you have any questions
There would probably be multiple ways to solve this, but I will only show you one of them.
First, we need to figure out how many tablespoons of the chemical solution it takes to decrease the number of bacteria in a gallon to 300. So we subtract 1200 by 300, to find the number of unnecessary bacteria, which is 900. Now we divide 900 by 75, which is 12. So it would take 12 tablespoons of the chemical solution to make a gallon have 300 bacteria.
There are 500 gallons, and we need to put 12 tablespoons of the chem-solution in each gallon. So we multiply 500 by 12, which is 6,000. Meaning that 6,000 tablespoons of chemical solution would be needed to make the 500-gallon tank have 300 bacteria per gallon.
Answer:
The value of x is 7 ⇒ 1st answer
Step-by-step explanation:
* Lets revise a fact in the circle
- The two tangents drawn from a point out side the circle are equal
∵ RSTUV is circumscribed about a circle
∴ Each side of the pentagon is a tangent to the circle
- Look to the attached figure to know how we will solve the problem
- Each tangent divided into two parts
# RS = x + y
∵ RS = 8
∴ x + y = 8 ⇒ (1)
# RV = x + n
∵ RV = 12
∴ x + n = 12 ⇒ (2)
- Subtract (2) from (1)
∴ y - n = -4 ⇒ (3)
# ST = y + z
∵ ST = 12
∴ y + z = 12 ⇒ (4)
# TU = z + m
∵ TU = 15
∴ z + m = 15 ⇒ (5)
- Subtract (5) from (4)
∴ y - m = -3 ⇒ (6)
# UV = m + n
∵ UV = 9
∴ m + n = 9 ⇒ (7)
- Add (6) and (7)
∴ y + n = 6 ⇒ (8)
- Lets solve equation (3) and equation (8) to find y
∵ y - n = -4 ⇒ (3)
∵ y + n = 6 ⇒ (8)
- Add (3) and (8)
∴ 2y = 2 ⇒ divide two sises by 2
∴ y = 1
- Lets substitute the value of y in equation (1)
∵ x + y = 8 ⇒ (1)
∵ y = 1
∴ x + 1 = 8 ⇒ subtract (1) from both sides
∴ x = 7
* The value of x is 7